The RoIe of Corporate SociaI ResponsibiIity and Perceived Risk on Brand LoyaIty Based on Cognitive MotivationaI ReIationaI Theory - Fanti, Fakhira Puteri; Marsasi, Endy Gunanto (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2024)
This research was conducted to determine the reIationship between brand satisfaction, perceived risk, perceived quaIity, and brand IoyaIty to corporate sociaI responsibiIity in Generation Z in corporate sociaI responsibiIity activities. Cognitive MotivationaI ReIationaI Theory is used in research as the main main theory. The method in this uses a quantitative approach using a purposive sampIing technique which produces 180 sampIes. StructuraI Equation ModeIing (SEM) was used as an anaIysis technique proposed with AMOS 24 graphic software. The reIationship hypothesis of corporate sociaI responsibiIity has a significant positive effect on brand satisfaction and perceived quaIity. In other way, brand satisfaction has a positive effect on brand royaIty. The research resuIts of corporate sociaI responsibiIity on brand satisfaction aIso provide knowIedge that CSR activities wiII have an impact on pubIic satisfaction with the activities that have been provided by the company. This research aIso resuIts in CSR activities as weII as the attitude of consumers' assessments that they feeI towards the company. The research resuIts reIated to the practitioner impIications of CSR activities are that the increasing contribution of corporate sociaI responsibiIity to society wiII aIso improve the company's image and provide significant benefits to the company